Media and development in Asia regional perspectives - Banerjee, Indrajit 1964-; Rao, Madanmohan; Asian Media Information and Communication Centre (Singapore Asian Media Information and Communication Centre, 2008)
This book brings together some of the most outstanding and novel papers on media and development presented at the AMIC Annual Conferences in Bangkok, Thailand, in July 2004. It features over a dozen contributions from around the region, providing a wealth of fresh case studies as well as breaking new ground in highlighting emerging frontiers of media development discourse in Asia, comparing regional development along multiple dimensions and frameworks, and pointing the direction towards further media initiatives at a national level.

The papers selected are grouped into three key themes: media and development; new narratives and political discourse; and media impacts and capacity building. Part I addresses macro-level impacts and policies pertaining to media and development in Asia. Part II deals with more direct media issues such as new narratives and emerging forms of political discourse and groupings ins Asia. Part III shifts the focus to traditional media impacts on youth and tribal audiences, as well as new media impacts on the education and business sectors.

The contributors to this book have highlighted not just an interesting range of media and development issues in Asia, but have also introduced a good variety of media research methods. These include quantitative assessments of media impacts in society, comparative and longitudinal frameworks for evaluating regional ICT competitiveness, structural analyses of political and activist communication systems, in-depth case studies of individual organisations, and broad-based surveys of stakeholders in ICT4D.
Includes bibliographical references.
Keywords: Communication in economic development -- Asia; Mass media -- Asia; Mass media in community development -- Asia